A micro process-product study of a CLIL lesson l. Issue 1 (16th March 2018) - Long, Michael H.; Al Thowaini, Assma; Al Thowaini, Buthainah; Lee, Jiyong; Vafaee, Payman
Abstract : We begin by comparing two models for the simultaneous teaching of language and content: immersion, and content and language integrated learning (CLIL). Following a brief summary and critique of research on CLIL, we describe a micro process-product laboratory experiment with young adult native speakers of Arabic for whom English was the L2. The same fifteen-minute lesson about an amateur anthropologist's alleged discovery of a hitherto unknown indigenous tribe in the Amazonian jungle was delivered by nine surrogate teachers to nine groups of four surrogate students in three baseline English native speaker groups, three baseline Arabic native speaker groups and three CLIL groups. Findings on language use in the nine lessons are related to content learning and vocabulary knowledge. The short-term, artificial nature of the study precludes generalisations to real CLIL programs, which was not our intention. Rather, we wish to suggest that process-product laboratory studies of larger scale and longer duration, paired with classroom studies employing a similar design and research methodology, offer a useful approach to identifying strengths and weaknesses of CLIL programs largely ignored to date.